2022
DOI: 10.1002/solr.202100891
|View full text |Cite
|
Sign up to set email alerts
|

Featuring Semitransparent p–i–n Perovskite Solar Cells for High‐Efficiency Four‐Terminal/Silicon Tandem Solar Cells

Abstract: Two issues need to be resolved when fabricating p-i-n semitransparent perovskite solar cells (ST-PVSCs) for four-terminal (4 T) perovskite/silicon tandem solar cells: 1) damage to the underlying absorber (MAPbI 3 ), electron transporting layer ([6,6]-phenyl-C 61 -butyric acid methyl ester, PCBM), and work function (WF) modifier (polyethylenimine, PEI), resulting from the harsh sputtering conditions for the transparent electrodes (TEs) and 2) low average nearinfrared transmittance (ANT) of TEs. Herein, a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The references from the list were reported between the years 2021 and 2024. 59 Some research groups have demonstrated promising alternative electrodes that maintain good electrical and high transmittance in the NIR region. 60,61 These electrodes are expected to contribute to the improvement of the EQE and responsivity of the NIR-OPDs.…”
Section: Resultsmentioning
confidence: 99%
“…The references from the list were reported between the years 2021 and 2024. 59 Some research groups have demonstrated promising alternative electrodes that maintain good electrical and high transmittance in the NIR region. 60,61 These electrodes are expected to contribute to the improvement of the EQE and responsivity of the NIR-OPDs.…”
Section: Resultsmentioning
confidence: 99%
“…Among these TCOs, sputtered ITO is widely used due to its high transmittance at visible light wavelengths and low electrical resistivity. [92,93] To reduce damage to the underlying layer, protective layers like MoO X , [94,95] SnO 2 , [96,97] and ZnO [98,99] need to be deposited before ITO sputtering. The high doping concentration in ITO enhances its conductivity, but at the same time causes high free-carrier absorption in the near-infrared region.…”
Section: Parasitic Absorptionmentioning
confidence: 99%
“…Reproduced with permission. [ 97 ] Copyright 2019, John Wiley and Sons. e) Transmission of aluminum‐doped zinc oxide (AZO) film and glass substrate.…”
Section: Performance Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the properties of SnO 2 show excellent stable after deposition. For example, Lee et al [17] fabricated single-junction perovskite solar cell by introducing SnO 2 as buffer layer. Thanks to the ability of SnO 2 to mitigate sputtering damage, they obtained a power conversion efficiency (PCE) of 17.23%.…”
Section: Introductionmentioning
confidence: 99%